Analisis Penerapan Pengakuan Pendapatan Kontrak Konstruksi Berdasarkan PSAK 34 - Subagja, Riki; Pradipto, Didit (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
This study aims to analyze the implementation of contract revenue recognition based on PSAK 34. The problem that is often faced by companies that are particularly engaged in the field of construction services in the recognition of income is the method of revenue recognition what should be used or applied, because there are differences in recognition between the one method with others. Especially if a project is done is more than a year or the so-called Long-term project. In addition, the presentation of financial statements of income recognition in each accounting period must be reported in accordance with generally accepted Accounting Standards (PSAK No. 34 concerning Construction Contracts). There is only one method used or applied that is the percentage completion method. The percentage method recognizes income with two approaches, based on physical progress and cost-to-cost. PT X as a construction service company uses the percentage of completion method with a physical progress approach (Physical progress) in the recognition of his opinion for both long-term contract and short-term contract. The results of this study conclude that the accounting treatment of the application of revenue recognition of construction services by using the percentage of completion method with physical progress approach on PT X is in conformity with the accounting standards set in PSAK No. 34. However, when compared to revenue recognition using the percentage of completion method with a cost-to-cost approach the firm can recognize the revenue and expenses more to illustrate or show a more proportional calculation because it corresponds to the costs incurred or poured out. Keywords: revenue recognition, expense recognition, PSAK no. 34